1996
DOI: 10.1111/j.1399-6576.1996.tb04474.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung uptake of lidocaine during hyperoxia and hypoxia in the dog

Abstract: These findings suggest that percent lung uptake of lidocaine is unaffected by hypoxic ventilation and by varying the concentration of lidocaine in the perfusion through the recipient dog lung lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this study, animals were ventilated in a hyperoxic condition. Concerning the effects of inspiratory oxygen concentration on the pulmonary uptake of local anesthetics, it has been reported that there is no significant difference in the pulmonary uptake of lidocaine between hyperoxic and hypoxic dogs (24).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, animals were ventilated in a hyperoxic condition. Concerning the effects of inspiratory oxygen concentration on the pulmonary uptake of local anesthetics, it has been reported that there is no significant difference in the pulmonary uptake of lidocaine between hyperoxic and hypoxic dogs (24).…”
Section: Discussionmentioning
confidence: 99%